Canada and the United Nations in the post-Cold War: Failure or neglect? - McKinstry, Shawn Darric (University of Ottawa (Canada), 2003)
Peacekeeping has come to be recognised as an essential multilateral activity by which to maintain world peace. Canada, a leading nation in peacekeeping, established an enviable record during the Cold War participating on virtually every mission deployed by the UN. There is, however, a belief today that peacekeeping efforts in the post-Cold War era have failed. In turn, the Canadian government has been criticised for its continued willingness to participate in UN led operations as it seems to be occurring without a policy framework. As opposed to the Cold War where policy rationales could be made for Canadian peacekeeping efforts, modern efforts appear unproductive, dangerous, and contradicted by Canada's fiscal military expenditures. This thesis explores this shift by examining the history of the Military Staff Committee, the differences between an interstate and intrastate conflict, force composition and finally Canada's policy and approaches towards peacekeeping. Collectively, they demonstrate that the UN and Canada have not failed in the post-Cold War era; rather, the approaches that made peacekeeping successful for forty years have hindered it for the last ten.
Keywords: History, Canadian.; History, Modern.; Political Science, International Law and Relations.